PERANAN SEKTOR BAJA DALAM PEREKONOMIAN INDONESIA - . Hasni; Hiras Manulang (Buletin Ilmiah Litbang Perdagangan, 2011)
this study investigates the role of steel industri on Indonesia’s economy through its linkages with other sectors. It also discusses industrial strategies to develop steel industry and trade. By using ackward and forward linkages methods, drawn from an input-output table, the importance of iron and steel industry for other sectors of the Indonesian national industry is clear. moreover, investment in various sectors, the price of steel, and the exchange rate affect the existence and growth of the steel industry. macroeconomy indicators, such as the consumption of cement, car and retail sales, as well as the performance of the construction sector also give important contributions to the growth of the iron and steel industry sector.